2016
DOI: 10.1038/srep21954
|View full text |Cite|
|
Sign up to set email alerts
|

The green peach aphid Myzus persicae perform better on pre-infested Chinese cabbage Brassica pekinensis by enhancing host plant nutritional quality

Abstract: The green peach aphid, Myzus persicae Sulzer, is a notorious pest on vegetables, which often aggregates in high densities on crop leaves. In this study, we investigated whether M. persicae could suppress the resistance level of Chinese cabbage Brassica pekinensis. M. persicae performed better in terms of weight gain (~33% increase) and population growth (~110% increase) when feeding on previously infested (pre-infested) Chinese cabbage compared with those on non-infested plants. However, when given a choice, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 46 publications
1
74
0
Order By: Relevance
“…Both Bemisia tabaci (Gennadius) and Myzus persicae (Sulzer) are serious pests affecting the production of tobaccos and other crops (Kollenberg et al, 2014; Santos-Garcia et al, 2015; Cao et al, 2016; Kang et al, 2016). Also maize fields have been reported to be damaged by the colonization of biotype B whiteflies (Quintela et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Bemisia tabaci (Gennadius) and Myzus persicae (Sulzer) are serious pests affecting the production of tobaccos and other crops (Kollenberg et al, 2014; Santos-Garcia et al, 2015; Cao et al, 2016; Kang et al, 2016). Also maize fields have been reported to be damaged by the colonization of biotype B whiteflies (Quintela et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to fast evolution, B. tabaci nowadays has diverse biotypes worldwide among which the B and Q types can cause severe crops losses (Santos-Garcia et al, 2015). Green peach aphid M. persicae , which is another kind of important pest affecting tobaccos, has a broad spectrum of hosts all over the world (Cao et al, 2016; Kang et al, 2016; Kayser et al, 2016). The pests can both deprive plants of nutrients and transmit cucumber mosaic viruses or other pathogens (Zhao et al, 2015), resulting in immense losses of crop yield (Cao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, aphid feeding on M. hapla-infested plants induced the JA, but not the SA pathway. Indeed, it has been reported that aphid feeding triggers both SA and JA responses (Moran et al, 2002;De Vos et al, 2005;Cao et al, 2016). On Arabidopsis thaliana, B. brassicae feeding particularly increases the expression of genes in the SA pathway, and to a lesser extent in the JA pathway (Kuśnierczyk et al, 2008).…”
Section: Interactive Effects Of Nematodes and Aphidsmentioning
confidence: 99%
“…Nematodes alter primary metabolite production and resource allocation within their host plant to enhance nutrient allocation to their feeding site (Kyndt et al, 2012a;Hol et al, 2013). Aphids also create a nutrient sink, enhancing amino acid and sugar concentrations in the phloem sap on which they feed (Cao et al, 2016;Hol et al, 2016). When nematodes and aphids feed on the same plant, it may also result in a "tug of war" for plant nutrients between the two herbivores.…”
Section: Nematodes and Aphids May Compete For Nutrientsmentioning
confidence: 99%